(untitled) (Journal of International Studies, 2020)
The challenges of poverty and insurgency have caused problems of different dimensions in north-eastern Nigeria. Specifically, the Bauchi state had recorded 89.5 percent of Multidimensional Poverty Indicators, more than any other state in the country. The main objective of this study is to explore the strategies that could build resilience to poverty in the study area. To achieve this, a qualitative research design, via semi-structured interview and purposive sampling, were applied. Accordingly, twenty-two informants from the ministries, agencies and commissions, in addition to some selected underprivileged people, were consulted during the data collection. Consequently, the findings from the study indicate that national, state, community and individual strategies were suggested to overcome poverty and other socioeconomic challenges that are faced by the people in Northeastern Nigeria in general, and Bauchi state in particular. The views of the informants ensured that the necessary measures can be taken to address the socioeconomic challenges identified in the state. Some of the community strategies include security initiatives, collaborations with NGOs to cushion the effects of poverty in the towns and villages, and the contributions from religious and traditional institutions. Furthermore, personal empowerment, enhancing peoples’ confidence, and skills were identified as the individual strategies. Subsequently, by strengthening the federal government, states as well as security arrangements could avert the problems discovered. The expansion of poverty reduction programs, accessible educational policies, youth empowerment schemes, rehabilitation, reconstruction, and the overall development of northeastern Nigeria were suggested.